Electron transport in sulfate‐reducing bacteria: Molecular modeling and NMR studies of the rubredoxin — tetraheme‐cytochrome‐c3 complex - Stewart, David E. (2019)
A hypothetical model of the complex formed between the iron‐sulfur protein rubredoxin and the tetraheme cytochrome c3 from the sulfate‐reducing bacteria Desulfovibrio vulgaris (Hildenborough) has been proposed utilizing computer graphic modeling, computational methods and NMR spectroscopy. The proposed complex appears feasible on the basis of complementary electrostatic interaction and steric factors and is consistent with the data from NMR experiments. In this model, the non‐heme iron atom of rubredoxin is in close proximity to heme 1 of cytochrome c3. The complex is stabilized by charge‐pair interactions and hydrogen bonds. This complex is compared to the flavodoxin‐cytochrome c3 complex previously proposed [Stewart, D. E., LeGall, J., Moura, L., Moura, J. J. G., Peck, H. D. Jr, Xavier, A. V., Weiner, P. K. & Wampler, J. E. (1988) Biochemistry 27, 2444–2450] and new NMR data shows that both proteins interact with the same heme group of the cytochrome as postulated.